Ageing-freezing/thaw process affects blooming time and myoglobin forms of lamb meat during retail display. (July 2019) - Alvarenga, Tharcilla I.R.C.; Hopkins, David L.; Ramos, Eduardo M.; Almeida, Amélia K.; Geesink, Geert
Abstract: Loins from fifty-six lambs were allocated to 2 ageing times (6 and 12 days post mortem) and a Frozen treatment (6 days of ageing followed by freeze/thaw process). Instrumental colour parameters, chroma, hue angle, 630/580 and myoglobin isoforms were assessed repeatedly every 5 min during the first 40 min and every 10 min from 40 to 120 min after surface cutting. Colour stability was measured instrumentally during 4 consecutive days of simulated retail display. L * values were lower for Frozen treatment compared to meat aged for 6 and 12 days. Redness increased at a lower rate for Frozen treatment compared to samples aged for 6 days up to the breakpoint and took a longer time to stabilize. Meat subjected to the ageing-freezing/thaw process required a longer time to reach a fully bloomed status than meat aged up to 12 days post mortem. The ageing-freezing/thaw process improved the redness of lamb meat displayed for 4 days in cold storage.